Tindak Tutur Ekspresif Wacana Narasi Siswa Kelas VII SMP Negeri 2 Kartasura Berdasarkan Pengalaman Pribadi - TITIS UTAMI, FEBRYANTI, Prof. Dr. Abdul Ngalim M.M (2017)
This research has two aims, 1) Describe the form of expressive speech actin the narrative discourse written by students of seventh grade of SMPN 2 Kartasura and 2) Describe the meaning of expressive speech act written by students of seventh grade of SMPN 2 Kartasura. The method of this research is Agih Method by using BUL basic technique. The results of the study stated in 25 seventh grade of SMPN 2 Kartasura student's written story, which have been submitted. Based on the data analysis, there are several kinds of expressions. Those expressions are sad, happy, difficult, regret. This research found 18 happy expressions, five sad expression, 1 difficult expression and 1 regret expression. Keywords: speech acts, expressive, narrative